Upaya Konseling Dalam Menangani Korban Kekerasan Pada Anak Di Pusat Pelayanan Terpadu (PPT) “Jayandu Widuri” Kabupaten Pemalang - Zakia Latifah; Arri Handayani; Venty Venty (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Violence against children is rampant everywhere and is a problem that is difficult to address, but efforts are still being made by related parties, such as the role of the government, legal institutions and others. The aim of this research is to determine the supporting and inhibiting factors for counseling for victims of child violence as an effort to treat victims of violence against children at the Integrated Service Center (PPT) "Jayandu Widuri" Pemalang Regency. The type of research used is qualitative research. Data collection techniques in this research were carried out by means of interviews and documentation. In testing the validity of the data, researchers carry out source triagulation, which will later be used to obtain data from different sources but with the same technique. The data analysis technique uses the Milles and Huberman model with analysis stages in the form of data reduction, data presentation, and drawing conclusions. From the results of data analysis, it can be concluded that the counseling stage provided by PPT "Jayandu Widuri" is able to help children who are victims of violence by healing feelings of trauma after experiencing violent behavior. Supporting factors for handling child victims of violence are supported by the existence of non-binding aid funds from outside so that PPT 'Jayandu Widuri" is able to recruit professional staff in their fields. Apart from that, the inhibiting factors in handling child victims of violence can be seen from the lack of human resources and inadequate shelter facilities at PPT 'Jayandu Widuri"..